Intergovernmental grants and bureaucratic power - Matz Dahlberg; Heléne Lundqvist; Eva Mörk (Uppsala University, Department of Economics, 2008)
In their role as agenda setters and implementers of political decisions, bureaucrats potentially have the power to influence decisions in their own favor. It is however difficult to empirically test whether bureaucrats actually are involved in such actions. In this paper we suggest and apply a new way of testing the hypothesis that bureaucrats can and do in fact affect policy to their own benefit. Making use of a discontinuity in the Swedish grant system, we estimate causal effects of intergovernmental grants on different types of personnel employed by the local governments. On the margin, we find a large, positive effect of grants on the number of bureaucrats in the central administration, but no effects on the number of personnel in other important sectors run by the local government (child care, schools and elderly care). These results support the view that bureaucrats are able to, and do indeed, affect the allocation of grants within municipalities to support own goals.
urn:nbn:se:uu:diva-86712
Keywords: C33; H11; H70; H83; J45; 330; fiscal federalism; grants; bureaucrats; rent seeking; discontinuity analysis; Finanzbeziehungen; Finanzausgleich; Kommunalverwaltung; Allokation; Rent-Seeking; Schweden